The Nature of Optical Afterglows without Gamma-Ray Bursts: Identification of AT2023lcr and Multiwavelength Modeling - Maggie L. Li; Anna Y. Q. Ho; Geoffrey Ryan; Daniel A. Perley; Gavin P. Lamb; Nayana A.J.; Igor Andreoni; G. C. Anupama; Eric C. Bellm; Edo Berger; Joshua S. Bloom; Eric Burns; et al. (The Astrophysical Journal)
In the past few years, the improved sensitivity and cadence of wide-field optical surveys have enabled the discovery of several afterglows without associated detected gamma-ray bursts (GRBs). We present the identification, observations, and multiwavelength modeling of a recent such afterglow (AT 2023lcr), and model three literature events (AT 2020blt, AT 2021any, and AT 2021lfa) in a consistent fashion. For each event, we consider the following possibilities as to why a GRB was not observed: (1) the jet was off-axis; (2) the jet had a low initial Lorentz factor; and (3) the afterglow was the result of an on-axis classical GRB (on-axis jet with physical parameters typical of the GRB population), but the emission was undetected by gamma-ray satellites. We estimate all physical parameters using afterglowpy and Markov Chain Monte Carlo methods from emcee . We find that AT 2023lcr, AT 2020blt, and AT 2021any are consistent with on-axis classical GRBs, and AT 2021lfa is consistent with both on-axis low Lorentz factor (Γ _0  ≈ 5–13) and off-axis ( θ _obs  = 2 θ _jet ) high Lorentz factor (Γ _0  ≈ 100) jets.